Konseling Person Centered Therapy dalam Meningkatkan Kepercayaan Diri Mahasiswa Berkebutuhan Khusus Cerebal Palsy - Rischa Pramudia Trisnani; M. Ramli; Carolina Ligya Radjah (Jurnal Ilmu Keperawatan Jiwa, 2021)
Students with Special Needs Cerebral Palsy are individuals who take higher education but experience deviation in motor function, especially movement of muscles and have obstacles in the development of motion, causing limited activity. The purpose of this study was to increase the self-confidence of students with special needs Celebral Palsy through Person Centered Therapy counseling. This research is a type of qualitative research with a case study method. The subject of this research is students with special needs Celebral Palsy with the initials "P" who are 19 years old and have low self-confidence. While the research data collection techniques using interviews, observation, and documentation. The data analysis techniques used were Pattern Matching, Explanation, and Time Series Analysis. The result of this study was that “P” students had wrong perceptions about friends, lecturers and the environment because of their physical conditions. The impact is that “P” students feel anxious and depressed so they hesitate to express their opinions when doing activities both on campus and outside campus, are easily discouraged, are awkward in acting, are afraid of presenting in front of the class, and are afraid to ask or answer questions.